3D contrast-enhanced lung perfusion MRI is an effective screening tool for chronic thromboembolic pulmonary hypertension: results from the ASPIRE Registry. Issue 7 (24th January 2013) - Rajaram, Smitha; Swift, Andrew J; Telfer, Adam; Hurdman, Judith; Marshall, Helen; Lorenz, Eleanor; Capener, David; Davies, Christine; Hill, Catherine; Elliot, Charlie; Condliffe, Robin; Wild, Jim M; et al.
Abstract : Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is a complication of pulmonary embolism potentially curable by surgery. Perfusion scintigraphy is currently advocated as the imaging modality of choice to exclude CTEPH due to its high sensitivity. We have evaluated the diagnostic utility of lung perfusion MRI. Methods: Consecutive patients attending a pulmonary hypertension referral centre undergoing lung perfusion MRI, perfusion scintigraphy, CT pulmonary angiography (CTPA) and right heart catheterisation within 14 days were identified. Results: Of 132 patients, 78 were diagnosed as having CTEPH. Lung perfusion MRI correctly identified 76 patients as having CTEPH with an overall sensitivity of 97%, specificity 92%, positive predictive value 95% and negative predictive value 96% compared with perfusion scintigraphy (sensitivity 96%, specificity 90%) and CTPA (sensitivity 94%, specificity 98%). No cases of surgically accessible CTEPH were missed with either modality. Conclusions: Lung perfusion MRI has high sensitivity equivalent to perfusion scintigraphy in diagnosing CTEPH but does not require ionising radiation, making it an attractive initial imaging modality to assess patients with suspected CTEPH.